Weight perception and weight management via information nudges - WANG, Lanjie (Institutional Knowledge at Singapore Management University, 2024)
Being overweight or obese is a serious public health problem. Misperception of one's own weight status and inertia are major obstacles to weight control. To overcome these two problems, we conduct a randomized controlled trial in which participants are presented with the correct weight category based on their body mass index to remove any weight misperception, and then given six biweekly reminders about healthy diet and physical activity via SMS/email. We find that our intervention reduces individuals’ weight misperception and encourages healthier dietary choices. However, it has little impact on their physical activity. We further show that people who were obese and those who underestimated their weight status in the baseline survey maintain healthier dietary choices for at least six months after the intervention.